Immunotherapeutic and Preventive Role of Purified Extract Rich in Beta-Glucans Derived from D-Fraction of Grifola frondosa Mushroom in Experimental Mice Biomodel of Mammary Carcinogenesis - Aguilera Braico, Diego Máximo (2017)
The overall vision of the modern science needs to change to a revalorization of the natural compounds and their beneficial effects on human diseases, such as cancer. Medicinal mushrooms have been used since thousands of years due to its healing properties. Maitake (Grifola frondosa) is presented as one of the most interesting medicinal mushrooms that have been studied. Until now, Maitake D-Fraction may have anticarcinogenic activity, preventing oncogenesis and metastasis in certain tumor types. However, the exact molecular mechanism by which D-Fraction acts are yet unknown. The results shown in this chapter suggest that Maitake D-Fraction Pro4X, administered intraperitoneally, prevents significantly the development of mammary tumorigenesis, increases survival, and reduces the process of angiogenesis in BALBc mice. Although yet to determine the active component of the extract and the molecular mechanism by which it operates in the breast carcinogenesis process. The socioeconomic impact of this research project could be important, considering that in Argentina similar studies using natural compounds derived from medicinal mushrooms for cancer therapy have not yet been performed. The beneficial effects of Maitake, if proven, could be useful for the treatment of cancer patients who are undergoing chemotherapy or radiation or for breast cancer prevention in high-risk population.